2017
DOI: 10.1063/1.4975104
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure investigation of biphenylene films

Abstract: Photoelectron Spectroscopy (PS) and Near-Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy have been used to investigate the occupied and empty density of states of biphenylene films of different thicknesses, deposited onto a Cu(111) crystal. The obtained results have been compared to previous gas phase spectra and single molecule Density Functional Theory (DFT) calculations to get insights into the possible modification of the molecular electronic structure in the film induced by the adsorption on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…One of these combinations is the so called graphenylene, which has a small band gap and delocalized frontier orbitals [28][29][30]. A possible route to the synthesis of graphenylene was proposed elsewhere [28] and its experimental realization, although obtained through a different route, was reported recently [31,32]. Further, Schlütter et al reported recently that they were able to synthesize octafunctionalized biphenylene GNRs [33].…”
Section: Introductionmentioning
confidence: 99%
“…One of these combinations is the so called graphenylene, which has a small band gap and delocalized frontier orbitals [28][29][30]. A possible route to the synthesis of graphenylene was proposed elsewhere [28] and its experimental realization, although obtained through a different route, was reported recently [31,32]. Further, Schlütter et al reported recently that they were able to synthesize octafunctionalized biphenylene GNRs [33].…”
Section: Introductionmentioning
confidence: 99%
“…The C K-edge NEXAFS spectra of BPBr 2 /Cu(111) prepared at RT, 250 • C and 515 • C is shown in Figure 3. The polarizationdependent NEXAFS [18] showed that the π * resonance of the RT sample was strongly enhanced at normal incidence (NI) of the light, pointing to an almost standing adsorption geometry of the molecules (68 • ± 15 • ) [19,20]. At 250 • C, the polarization dependency was inverted and the π * resonance was, instead, enhanced at grazing incidence (GI).…”
mentioning
confidence: 99%
“…In case of nanoporous structures derived from graphene and with well-defined porous network, the porous graphene (PG) [16][17][18][19][20] and graphenylene (GP) can be cited [20][21][22][23]. Unlike the graphene, both PG and GP have a non-null band gap, ~ 3 and ~ 0.8 eV, respectively, as shown in recent work [20].…”
Section: Introductionmentioning
confidence: 84%